Development And Characterization Of Duck Nuggets - Lukman, Ismed (2010)

(untitled)
Establishment of standards for duck nugget processing with data proximate and physicochemical characteristics based on chicken meat has been studied. The percentage range of moisture, protein, fat, ash and carbohydrate contents of commercial chicken nuggets ranged was between 34.71-56.51%, 12.52-16.62%, 18.14-25.00%, 1.20-1.58% and 7.52-26.49%, respectively. The L*, a* and b* values of commercial chicken nuggets ranged between 64.38-68.41, 0.51-3.51 and 16.46- 19.35, respectively. The toughness of commercial chicken nuggets was ranged between 12.66-18.00 and water holding capacity was ranged between 34.54-51.57%. Cooking loss value was ranged between 3.37-13.05%. Texture profile analysis showed the hardness, cohesiveness, springiness, gumminess and chewiness was ranged between 33.36-77.45N, 0.61-0.80Ns, 1.00-1.23mm, 21.26-61.66N/mm2 and 23.02-66.13N/mm, respectively. The processing factors studied in the development of duck nugget including the types of flours, ratios of wheat flour used in the formulations, frying oils and washing treatments.